Retraining and Upgrading Workers A Guide for Postsecondary Educators. Research & Development Series No. 235 - Warmbrod, Catharine P.; Faddis, Constance R.; Ohio State Univ., Columbus. National Center for Research in Vocational Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
Designed for use by postsecondary educators involved in teaching displaced workers, this guidebook provides an in-depth look at successful upgrading and retraining programs in colleges in diverse situations across the country. The rationale for a human resource emphasis in economic development and the role of the two-year college in economic development are discussed. Provided next are case studies of upgrading and retraining programs at the following institutions: Tri-County Technical College in South Carolina, Macomb Community College in Michigan, State Technical Institute at Memphis in Tennessee, Triton College in Illinois, and South Oklahoma City Junior College in Oklahoma. Various barriers and solutions to developing successful retraining programs are examined, including state and local linkages for economic development, course approval systems, college forecasting and planning, marketing of customized training, customized training management, flexibility of resources, internal organization and cooperation, faculty and staffing, and other economic development outreach services. The last chapter presents these critical elements along with accompanying recommendations and provides conclusions reached concerning the upgrading and retraining of adult workers by colleges for industry. (MN)
Availability: National Center Publications, The Ohio State University, 1960 Kenny Road, Columbus, OH 43210 ($12.50).
Sponsoring Agency: Office of Vocational and Adult Education (ED), Washington, DC.
Contract Number: 300-78-0032.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Case Studies; Continuing Education; Coordination; Economic Development; Educational Needs; Educational Practices; Educational Strategies; Guidelines; Human Resources; Improvement; Improvement Programs; Job Skills; Job Training; Labor Force Development; Linking Agents; Outreach Programs; Postsecondary Education; Program Design; Program Development; Program Implementation; Retraining; School Role; Skill Development; Staff Utilization; Two Year Colleges; Displaced Workers; Macomb County Community College MI -- South Oklahoma City Junior College OK -- State Technical Institute at Memphis TN -- Tri County Technical College SC -- Triton College IL; Guides, Non-Classroom.